What goes up... (1st February 2023) - Cartwright, Jon
Abstract : Financial bonds are usually seen as safe and dependable investments, but a recent crash in the value of "ultra-long" bonds was bigger than conventional mathematical models could have predicted. They should have used rollercoaster physics, as Jon Cartwright explains.